2019
DOI: 10.1111/ijfs.14099
|View full text |Cite
|
Sign up to set email alerts
|

Free radical scavenging activities of phytochemical mixtures and aqueous methanolic extracts recovered from processed coffee leaves

Abstract: Summary It is well known that the choice of extraction solvents greatly affects both phytochemical composition and related bioactivity of plant extract. Herein, we show that coffee leaf extracts derived from 80% methanol have no effect on basal nitric oxide production in Raw 264.7 cells, whereas, a different result was observed with a previous hot water extract. Phytochemical mixtures formulated to contain equivalent amounts of CQAs, mangiferin and rutin know to present in coffee leaves showed a relatively low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The extraction yields of phytochemicals, TPC, and DPPH free radical scavenging capacity of coffee leaf extracts were increased as the extraction temperature, ethanol concentration, L:S ratio, extraction time and ultrasound power increased, whereas, in case of the age of leaves, the results were vice versa. Our previous studies also showed that mature leaves contained less chlorogenic acids, mangiferin, rutin, TPC and antioxidant activities compared with their young counterparts (Chen et al., 2019; Chen et al., 2018).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The extraction yields of phytochemicals, TPC, and DPPH free radical scavenging capacity of coffee leaf extracts were increased as the extraction temperature, ethanol concentration, L:S ratio, extraction time and ultrasound power increased, whereas, in case of the age of leaves, the results were vice versa. Our previous studies also showed that mature leaves contained less chlorogenic acids, mangiferin, rutin, TPC and antioxidant activities compared with their young counterparts (Chen et al., 2019; Chen et al., 2018).…”
Section: Resultsmentioning
confidence: 67%
“…However, to date, the information regarding the extraction of bioactive components from coffee leaves are scant. In our previous researches, hot water (Chen, Ma, & Kitts, 2018) and 80% methanol (Chen, Kitt, Ji, & Ding, 2019) were used to extract phytochemicals from coffee leaves, however, both studies did not focus on the extraction methods for phytochemicals. Marcheafave et al (2019) investigated the solvent effects on the pigments and antioxidant activities of coffee leave extract using experimental mixture design.…”
Section: Introductionmentioning
confidence: 99%
“…The NO inhibitory activity of AuNPs was evaluated according to the method described by Chen et al [30] . Raw 264.7 cells were grown in the complete DMEM which contains 100 U/mL penicillin, 100 g/mL streptomycin, and 10% FBS in a 37℃ cell culture oven containing 5 % CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The half-maximal inhibition concentration (IC 50 ) of each sample was calculated to estimate the anti-inflammatory capacity of AuNPs. Cell viability was measured by MTT assay [30] and only the viability of the cells > 90% were used.…”
Section: Methodsmentioning
confidence: 99%
“…Arabica coffee drink cup (200 ml) contains 70-200 mg chlorogenic acid (Clifford, 1999). It is also reported that the chlorogenic acid as sources of natural antioxidants (Chen et al, 2019). Therefore, these coffee beans in this research could be developed as a functional drink with beneficial effect in the body.…”
Section: Caffeine and Chlorogenic Acidmentioning
confidence: 85%